PERLINDUNGAN HUKUM TERHADAP KONSUMEN ATAS PRODUK MINUMAN KOPI YANG MENGANDUNG PARACETAMOL DAN VIAGRA - Mohammad Edgar Rahandika Fridayangga; Evi Kongres (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2022)
Consumer protection is a matter related to the business sector, especially in the field of food and beverage sales. Not a few consumers who suffered losses due to lack of awareness of consumers. The increasingly diverse distribution of food and beverages makes consumers not pay attention to the labels on these foods and beverages, especially on the halal label, changes in ingredients used and expiration dates. This can trigger business actors to commit fraud. Therefore, legal protection efforts are needed for consumers from various institutions such as LPPOM MUI which is in charge of handling halal certification, the POM Agency is in charge of supervising the circulation of products and BPSK as a dispute resolution agency in consumer legal sources based on Law No. 8/1999 on Consumer Protection. The purpose of the research is to find out the implementation process, what are the obstacles and solutions in legal protection for consumers in terms of Law No. 8/1999. The implementation of legal protection for consumers from the circulation of expired food and beverages in terms of Law No. 8/1999 on consumer protection through various stages and related to many sectors. For this reason, a good collaboration is needed. The implementation process starts from halal certification, labeling, and direct supervision to several shops and supermarkets by the POM and consumer dispute resolution by BPSK. Constraints in legal protection for consumers from the circulation of expired food and beverages in terms of Law No. 8/1999 on Consumer Protection are the many new products that are varied, incomplete documents, the size of the area, and the number of shops and supermarkets in several areas as well as the lack of parties involved. can descend directly, making it difficult to reach and supervise. The ideal legal protection for consumers from the circulation of expired food and beverages in terms of Law No. 8/1999 on Consumer Protection with direct supervision and inspection, consumers must be thorough and careful before buying products, and producers must pay attention to the safety and comfort of consumers and must also using safe and harmless raw materials. The provisions contained in Article 7 UUPK letter d that business actors are required to guarantee the quality of goods and/or services produced and/or traded based on the provisions of quality standards of goods and/or service